5α-Oleandrin reduce Bcl-2 protein and increase Bax protein expression on Hela cervical cancer cell - Wahyuningsih, Mae Sri Hartati; Mubarika, Sofia; Ganjar, Ibnu G.; Wahyuono, Subagus; Takeya, Tatsuo (Faculty of Medicine, Trisakti University, 2017)
BACKGROUNDThe leaves of Nerium indicum Mill. have been utilized traditionally to cure cancer. By using Bioassay guided extraction and isolation method, three compounds (NiO-1, NiO-2, NiO-3) were isolated from an active fraction of the CHCl3 extract of N. indicum leaves. NiO-2 identified as 5α- oleandrin is the best cytotoxic compound on HeLa cervical cancer cell in vitro among the other two. However mechanism of action of the compound hasn’t been evaluated yet. The aims of this study were to determine the mechanism of action at molecular level.METHODSThe action mechanism of 5α-oleandrin on HeLa cervical cancer cells was analyzed by staining the cells with Hoechst 33342; the agarose gel electrophoresis was aimed to determine the DNA fragmentation and the western blotting was aimed to determine the Bcl-2 and Bax protein expression.RESULTSIncubation of HeLa cervical cancer cell with 5α-oleandrin at the concentration 3,47x10-4 mM (24 hours) followed by staining with Hoechst 33342, a broken up light blue color of nucleus was observed (compared with intensive color of untreated control). By gel electrophoresis (at the same concentration of the tested compound), a smear band at about 200 bp was observed. In addition, cells treated with 5α-oleandrin displayed a decreasing of the Bcl-2 protein expression and increasing of the Bax protein expressionCONCLUSION5α-oleandrin induced HeLa cervical cancer cells DNA fragmentation observed by the presence of a smear band at about 200 bp indicative the apoptotic occurrence. 5α-oleandrin induces apoptosis by reducing the Bcl-2 protein expression but the Bax protein expression increases.